Analisis Pengaruh Pembangunan Infrastruktur Transportasi Terhadap Produk Domestik Regional Bruto Kabupaten Way Kanan Provinsi Lampung - Febriansyah Febriansyah; Gustaf Gautama (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
The availability of inadequate and quality transportation infrastructure positively affects a region's gross domestic product (GRDP) to below. This study aims to analyze the influence of transportation infrastructure development, namely road infrastructure, seaport infrastructure and airport infrastructure on Way Kanan District GRDP. The research method used in this study is a quantitative method. The results of multiple regression calculations show that 1) the road infrastructure has a significant number of 0.010 below 0.05; meaning that the independent variable has a substantial effect on GRDP. 2) seaport infrastructure, the considerable amount is 0.309 above 0.05; saying that these variables have not significantly affected gross regional domestic products. 3) Airport infrastructure, a significant number of 0.093 above 0.05; it means that the variable has not changed the GRDP. While the contribution of the research is a reference in development policies, especially the development of transportation infrastructure to increase the GRDP of Way Kanan District.